Copper alloy material and preparation method and application thereof

By controlling the composition and microstructure of copper alloy materials, the existing tin-silicon brass welding wire materials have been solved, and the welding materials with high conductivity, low melting point, high strength and excellent corrosion resistance are achieved to meet the welding materials needs of modern industry.

CN119506653AActive Publication Date: 2025-02-25JINTIAN COPPER GROUP CORP NINGBO

Patent Information

Application Number
CN202411378828.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-25
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The existing tin-silicon brass welding wire materials have good weld moldability but low conductivity, average weld strength, insufficient corrosion resistance and processing performance, which cannot meet the needs of modern industrial welding materials.

Method used

By controlling the composition of the copper alloy material, especially the content of Sn and Si, and the microstructure structure, the conductive, strength and corrosion resistance of the material are regulated. The Sn and Si elements are uniformly distributed to form diffusion strengthening, improving the strength and conductivity of the material, and controlling the area ratio of the α phase and β phase, optimizing the number of particles of Si and Sn, reducing the brittleness of the weld and pore formation.

Benefits of technology

It has achieved high conductivity, low melting point, high strength and excellent corrosion resistance of copper alloy materials, good moldability and easy processing, and meets the needs of modern industrial welding materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506653A_ABST
    Figure CN119506653A_ABST
Patent Text Reader

Abstract

The invention discloses a copper alloy material and a preparation method and application thereof.The copper alloy material comprises, by mass, 56%-64% of Cu, 0.5%-2.0% of Sn, 0.1%-1.0% of Si and the balance Zn and inevitable impurities, and the content of the inevitable impurities is smaller than or equal to 0.1%; the microstructure of the copper alloy material comprises an alpha phase, a beta phase, a Sn phase and a Si phase, wherein the area proportion of the alpha phase is larger than or equal to 10% and smaller than or equal to 30%, the area proportion of the beta phase is larger than or equal to 60% and smaller than or equal to 80%, the number of Sn particles is larger than or equal to 5000 / mm < 2 > and smaller than or equal to 20000 / mm < 2 >, and the number of Si particles is larger than or equal to 2000 / mm < 2 > and smaller than or equal to 10000 / mm < 2 >. By controlling the alloy components, the content and the wire drawing process, the structure of a microstructure in the copper alloy material is regulated and controlled, and the area ratio of each phase and the particle number of Sn and Si are controlled, so that the prepared copper alloy material has high strength, excellent corrosion resistance and conductivity and lower melting point; and the method has the characteristics of good weld formability, easy processing and the like, and has wide application prospects in the welding field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of copper alloys, and in particular relates to a copper alloy material and a preparation method and application thereof. Background Art

[0002] The application of tin-silicon brass welding wire mainly involves manufacturing, electronics and electrical engineering, chemical industry, automobile manufacturing, aerospace, shipbuilding, household appliances and metal art production. In the process of mechanical manufacturing, tin-silicon brass welding wire is often used to weld various mechanical parts, such as bearings, gears and shaft parts, due to its excellent welding performance and physical properties. Parts in precision equipment or instruments often have higher requirements for welding quality. Tin-silicon brass welding wire can provide higher strength and higher precision welding to ensure the quality and performance of the product.

[0003] In the field of electronics and electrical engineering, good electrical conductivity is a key factor. Tin-silicon brass welding wire can be used to manufacture and repair conductive parts to ensure the normal operation of electrical equipment. Underwater welding operations in marine engineering face the challenges of high pressure and corrosive environment. Tin-silicon brass welding wire is widely used due to its good corrosion resistance. In the automotive manufacturing industry, tin-silicon brass welding wire is used to weld various automotive parts, such as engine parts, exhaust systems, etc., to improve the overall performance of the vehicle.

[0004] According to the above application fields, tin-silicon brass welding wire is mainly suitable for welding ferroalloys and steel, iron and iron, copper and iron. There are also many welding methods. One is to make the welding wire into a ring and use electromagnetic induction heating to melt the welding ring to form a weld. This requires the material itself to have a certain plasticity to meet the forming requirements of the welding ring. In addition, the welding wire material itself needs to have a low melting point characteristic to meet the material's good fluidity when melted, to meet the integrity of the filling between the parent materials, and to reduce the defects of poor surface formability. In addition, it also includes gas welding, manual arc welding, argon arc welding, etc. to meet different welding needs.

[0005] The traditional tin-silicon brass welding wire material (BCu60ZnSnSi) has good weld formability, but its weld and heat-affected zone have a large tendency to crack and pore, low conductivity, average weld strength, and average machinability and corrosion resistance, which has gradually failed to meet the needs of modern industrial level welding wire materials.

[0006] Patent document CN109434318A discloses a tin brass alloy solder, including 61.5-63wt% Cu, 0.7-1.0wt% Sn, 0.4-0.8wt% Si, 0.02-0.2wt% Ni, 0.02-0.2wt% Al, 0.02-0.15wt% As, 0.02-0.2wt% Ti, and the rest is Zn and unavoidable impurities, wherein the total content of Cu and Zn is greater than 97.0wt%. The tin brass alloy solder in the invention has a high melting point and low strength, and during welding, the probability of cracks and pores in the solder joint and heat-affected zone is high, resulting in a low yield rate of the product, and the invention does not study the conductive properties of the material.

[0007] In view of the shortcomings of brass solder in the prior art, it is of great significance to seek a brass material with good weld formability, good electrical conductivity, low tendency to thermal cracking and pores, high strength, high machinability and high corrosion resistance. Summary of the invention

[0008] The purpose of the present invention is to provide a copper alloy material and a preparation method and application thereof. The copper alloy material of the present invention has excellent electrical conductivity, low melting point, high strength and excellent corrosion resistance, and has the characteristics of good weld formability and easy processing, and can meet the needs of modern industrial development welding materials.

[0009] The first aspect of the present invention provides a copper alloy material, comprising the following components in percentage by mass: Cu: 56-64%, Sn: 0.5-2.0%, Si: 0.1-1.0%, the remainder being Zn and inevitable impurities, wherein the content of inevitable impurities is ≤0.1%; the microstructure of the copper alloy material comprises α phase, β phase, Sn phase and Si phase, wherein the area ratio of the α phase is 10%≤≤30%, the area ratio of the β phase is 60%≤≤80%, and 5000 pieces / mm 2 ≤Sn particles ≤20000 / mm 2 , 2000 pieces / mm 2 ≤ Number of Si particles ≤ 10000 / mm 2 .

[0010] The present invention regulates the performance of copper alloy materials by controlling the composition, content and microstructure of the alloy. Sn element is the main strengthening element of the material, and is evenly distributed in the matrix in the form of single-phase particles to produce dispersion strengthening. When the material is deformed, it hinders the slip of dislocations, produces dislocation accumulation, and improves the strength of the material. Under high temperature and corrosive environment, tin can form a dense tin oxide (SnO2) protective film on the surface of the copper matrix. This film is stable and can prevent further oxidation of the substrate, thereby enhancing the corrosion resistance of the material. During welding, tin improves the fluidity and wettability of the material. The excellent fluidity ensures that the welding wire can evenly fill the weld during the welding process to form a smooth weld surface. Good wettability allows the welding wire to be tightly combined with the base material, thereby improving the welding quality.

[0011] The Sn content of the present invention is between 0.5% and 2.0%. When the Sn content is lower than 0.5%, firstly, the strength and corrosion resistance of the material are not greatly improved, and secondly, the fluidity and wettability of the material during welding are insufficient, resulting in poor weld formability and bonding ability, and low weld strength and corrosion resistance. When the Sn content is higher than 2.0%, the strength and corrosion resistance of the material will be greatly improved, but due to the low melting point of Sn (231°C), the material will have too good fluidity during welding, resulting in poor weld formability and reduced weld service life.

[0012] Si is the main strengthening element of the material. It is evenly distributed in the matrix in the form of single-phase particles, producing dispersion strengthening. When the material is deformed, it hinders the slip of dislocations, produces dislocation accumulation, and improves the strength of the material. During welding, Si will react with oxygen in the molten pool to generate SiO2, which is discharged in the form of slag, reducing the formation of pores. In addition, it can effectively control the evaporation of zinc, ensuring the integrity of the weld and good mechanical properties.

[0013] The Si content of the present invention is 0.1-1.0%. When the Si content is lower than 0.1%, the strength of the material is less improved, and insufficient degassing during welding will cause pores in the weld, reducing the performance of the weld. When the Si content is higher than 1.0%, it is easy to react with oxygen during welding to generate more low-melting silicates. This not only increases the fluidity of the slag and molten metal, but also may cause splashing, thereby affecting the quality of the weld and easily generating cracks. In addition, a high silicon content can drastically reduce the welding performance of steel because it can promote the growth of columnar crystals in cast steel, reduce plasticity, and may also cause cracks, further affecting the quality and strength of the welded joint.

[0014] When the Zn content is between 36% and 46%, the material is α+β dual-phase brass, and when it exceeds 46%, it is β single-phase brass. The present invention controls the area ratio of each phase in the material and the number of Si and Sn particles by controlling the content of each element in the alloy and the subsequent annealing parameters. The α phase is a phase based on Cu and is a soft phase. Too much will reduce the strength of the weld, so the present invention limits the area ratio of the α phase to 10%≤≤30%. At the same time, the present invention controls the area ratio of the β phase to 60%≤≤80% to ensure the strength of the weld. The number of Si and Sn particles will affect the brittleness of the material and the weld and the fluidity of the metal during welding. The present invention can avoid aggregation of Si and Sn particles by controlling the number of Si and Sn particles within the above range, reduce the brittleness of the material and the weld, and make the weld formability better.

[0015] Preferably, the copper alloy material comprises P, and the content of P is 0.001-0.3%.

[0016] The P element is a deoxidizer in the material, and also plays a role in refining grains and increasing melt fluidity. P will react with oxygen in the melt to generate P2O5, which will volatilize to achieve the purpose of deoxidation. During solidification, it will hinder the growth of grains, achieving the purpose of grain refinement.

[0017] The present invention controls the P content in the copper alloy material to 0.001-0.3%. When the P content is lower than 0.001%, its effect on deoxidation, grain refinement and increase in melt fluidity is small; when the P content is higher than 0.3%, the proportion of Cu3P phase generated by reaction with Cu increases. Cu3P is a brittle phase that reduces the plasticity of the material and deteriorates the performance of the material. When welding steel, a large amount of P will be dissolved into the steel, resulting in cold brittleness and reducing the strength of the weld.

[0018] When P is added to the copper alloy material, P will react with Cu to generate Cu3P phase. Preferably, the area ratio of the Cu3P phase satisfies: 0.2%≤Cu3P phase area ratio≤3%. The Cu3P phase is a hard phase with wear-resistant characteristics. A small amount of Cu3P phase can improve the strength and wear resistance of the material, and can also improve the strength and wear resistance of the weld. When there is too much Cu3P phase, the material will become brittle, and the weld will also become brittle, affecting the performance of the weld. The present invention controls the area ratio of the Cu3P phase within the above range, which can improve the strength and wear resistance of the material and the quality of the weld.

[0019] Preferably, the oxygen content in the copper alloy material is ≤20ppm. In the present invention, P is added to remove oxygen from the melt, so that the oxygen content in the prepared copper alloy material is less than 20ppm. More preferably, the oxygen content in the copper alloy material is ≤10ppm. The increase in oxygen content in the weld will cause the strength, plasticity, toughness and other mechanical properties of the weld to decrease, especially the low-temperature impact toughness will drop sharply, which will cause the weld to break easily during use. At the same time, the presence of oxygen will also cause the molten drop to contain more oxygen and carbon, and the CO generated by their interaction will expand due to heat, causing the molten drop to explode, resulting in splashing and affecting the stability of the welding process.

[0020] Preferably, the copper alloy material includes rare earth elements, and the content of the rare earth elements is 0.01-0.1%.

[0021] The main function of rare earth elements is to refine the grains, remove harmful impurities (Bi and S) in the melt, and improve the purity of the melt and the uniformity of the material structure. The addition of rare earth elements can significantly improve the weld morphology, making it smoother and more uniform, and the width and height of the weld more stable, thereby improving the mechanical properties and corrosion resistance of the welded joint. This improvement is due to the optimization of metal fluidity and wettability by rare earth elements, making it easier for the metal to fill the weld, reducing the shrinkage and deformation of the weld, and effectively avoiding the occurrence of welding defects such as cracks. Rare earth elements also have an important influence on the mechanical properties of welded joints, which can improve the strength, toughness and plasticity of welded joints and reduce the occurrence of welding defects.

[0022] The present invention controls the rare earth element content to be 0.01-0.1%. When the rare earth content is lower than 0.01%, the strengthening effect is weak. When the content is higher than 0.1%, the copper liquid becomes viscous during smelting, which is not conducive to upward drawing.

[0023] Preferably, the rare earth element includes at least one of La, Ce or Y. More preferably, the rare earth element is at least one of La or Ce.

[0024] Preferably, the copper alloy material has a tensile strength of ≥600 MPa, an elongation A100 mm% ≥25%, a dezincification corrosion resistance of ≤20 μm, and a volume resistivity of ≤0.07 Ω·mm. 2 / m, melting point ≤860℃.

[0025] As a filler metal, the smaller the volume resistivity of the welding wire is under induction heating conditions, the greater the heating current will be, and the easier it will melt. The main factors affecting the volume resistivity are the composition and processing technology of the alloy, among which Sn, Si and Zn can increase the volume resistivity. The present invention reduces the volume resistivity of the material by limiting the addition amount of Sn, Si and Zn. At the same time, the greater the processing rate, the more internal defects of the material increase, resulting in an increase in volume resistivity. Annealing can reduce or eliminate the defects generated during the processing process by improving the microstructure of the material. The present invention subsequently improves the microstructure of the material by controlling the annealing parameters to further reduce the volume resistivity of the material. The lower the melting point of the welding wire, the easier it is to melt, and the higher the welding efficiency. The present invention controls the composition of the alloy and the subsequent preparation process, so that the prepared copper alloy material has a lower melting point and volume resistivity, is easier to melt during welding, and has a higher welding efficiency.

[0026] Preferably, the copper alloy material is copper alloy welding wire.

[0027] The second aspect of the present invention provides a method for preparing the copper alloy material, comprising the following steps: subjecting the alloy melt to upward continuous casting + electromagnetic stirring → large wire drawing + first online annealing → medium wire drawing + second online annealing;

[0028] Among them, the drawing speed of the large wire drawing is 6-10m / s, the annealing coefficient of the first online annealing is 10-20kU%, and the annealing voltage is 100-130V; the drawing speed of the medium wire drawing is 3-14m / s, the annealing coefficient of the second online annealing is 25-30kU%, and the annealing voltage is 90-125V.

[0029] The wire drawing speed and annealing coefficient are matched to each other. The slower the wire drawing speed, the lower the annealing coefficient, and vice versa. Too slow wire drawing will affect production efficiency, and too fast wire drawing speed will cause the material to be under high temperature conditions during annealing, which is not only easy to break the wire, but also easy to overburn, deteriorate the structure, and reduce the performance of the material. The annealing voltage is related to the wire drawing speed and annealing coefficient. Under different wire drawing speeds and annealing coefficients, the annealing voltage needs to be adjusted to ensure that the material obtains the best annealing effect.

[0030] Too low an annealing coefficient will make it impossible for the material to completely undergo recrystallization annealing during stretching, causing the material to retain more processed structures and higher strength. After continuous stretching, the strength performance will become very high, resulting in frequent wire breakage when passing through the mold during continuous stretching, making mass production impossible.

[0031] When the annealing coefficient is too high, the material will be completely recrystallized, and the two elements Sn and Si will aggregate. During welding, the local metal in the molten pool will have poor weld formability due to the excessive fluidity of Sn aggregation. Secondly, after Si aggregation, Si aggregation will occur locally in the weld. Si itself is a brittle phase, which greatly increases the brittleness of the weld and easily causes cracks in the weld. The part with less Si will produce pores due to insufficient degassing. And the higher the annealing coefficient, the higher the proportion of the β phase of the material, the smaller the proportion of the α phase, the fewer the number of Si and Sn particles, and it will be easier to aggregate, increasing the brittleness of the material and the brittleness of the weld. Therefore, the present invention limits the large-draw annealing coefficient to 10-20kU%, and the medium-draw annealing coefficient to 25-30kU%. In addition, the present invention can reduce the influence of the processing rate on the microstructure of the material by controlling the annealing coefficient, thereby reducing the volume resistivity.

[0032] The present invention realizes comprehensive optimization of material microstructure, mechanical properties, electrical conductivity and production efficiency by controlling the drawing speed, annealing coefficient and annealing voltage of large wire drawing and medium wire drawing, so that the prepared copper alloy material has high strength and electrical conductivity and low melting point, thereby improving the quality of the weld and the processing performance.

[0033] Preferably, the processing rate of the large wire drawing is ≥40%. The present invention controls the processing rate of the large wire drawing within the above range, which can break the cast structure and improve the uniformity of the material structure.

[0034] Preferably, the process of upward continuous casting of the alloy melt is: firstly, the raw materials meeting the proportion are smelted at a smelting temperature of 1020-1100°C, and after all the raw materials are melted, they are kept warm at a temperature of 1050-1100°C, and then upward continuous casting is performed, with a pulling speed of 4-6 mm / s, a dwell time of 0.5-1s, a crystallizer water inlet temperature of 10-25°C, and a water outlet temperature of 15-35°C. The present invention adopts the upward continuous casting process for casting, which is mature and has low cost.

[0035] Preferably, the frequency of the electromagnetic stirring is 1-5 Hz, and the current is 5-15 A. Electromagnetic stirring can refine grains and improve the uniformity of the structure.

[0036] The third aspect of the present invention provides the application of the copper alloy material in the field of welding. The copper alloy material of the present invention has excellent electrical conductivity, low melting point, high strength and excellent corrosion resistance, and has the characteristics of good weld formability and easy processing, and has broad application prospects in the field of welding.

[0037] Compared with the prior art, the present invention has at least the following beneficial effects:

[0038] (1) The present invention controls the alloy composition, content and wire drawing process to regulate the structure of the microstructure in the copper alloy material, control the area ratio of each phase and the number of Sn and Si particles, so that the prepared copper alloy material has high strength, excellent corrosion resistance and electrical conductivity, and a low melting point, and has the characteristics of good weld formability and easy processing.

[0039] (2) The copper alloy material of the present invention solves the problems of low weld strength, welding porosity, low corrosion resistance, and poor conductivity of traditional tin-silicon brass welding wire. Its tensile strength is ≥600MPa, elongation A100mm% ≥25%, anti-dezincification corrosion performance is ≤20um, and volume resistivity is ≤0.07Ω·mm 2 / m, melting point ≤860℃, meeting the needs of modern industrial development welding materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is the metallographic diagram of the copper alloy material prepared in Example 1.

[0041] Figure 2 This is the metallographic diagram of the copper alloy material prepared in Example 2.

[0042] Figure 3 This is the metallographic phase diagram of the copper alloy material prepared in Example 3. DETAILED DESCRIPTION

[0043] The preparation method of the copper alloy material in the embodiment of the present invention is as follows:

[0044] (1) The alloy melt is subjected to upward continuous casting + electromagnetic stirring: electrolytic copper, Sn ingot, copper-silicon master alloy (Si20%), phosphorus copper master alloy (P14%), and rare earth Ce / La elements are added to the smelting furnace according to the alloy composition ratio, and the smelting temperature is 1020-1100°C. After all the raw materials are melted, they are kept warm at a temperature of 1050-1100°C. Then, upward continuous casting is carried out, with a pulling speed of 4-6 mm / s, a pause time of 0.5-1s, a crystallizer water inlet temperature of 10-25°C, and a water outlet temperature of 15-35°C. Electromagnetic stirring is used during the upward continuous casting process, and the frequency of the electromagnetic stirring is 1-5Hz and the current is 5-15A.

[0045] (2) A six-link drawing machine is used for wire drawing and online annealing. The wire drawing speed of the large wire drawing is 6-10m / s, the processing rate is ≥40%, the annealing coefficient of the online annealing is 10-20kU%, and the annealing voltage is 100-130V.

[0046] (3) A medium drawing machine is used for finished wire drawing and online annealing. The wire drawing speed of the medium drawing is 3-14 m / s, the annealing coefficient of the online annealing is 20-30 kU%, and the annealing voltage is 90-125 V.

[0047] Example 1

[0048] The preparation method of the copper alloy material in this embodiment is as follows:

[0049] (1) Perform upward continuous casting + electromagnetic stirring on the alloy melt: according to the alloy composition ratio, 559 kg of cathode copper, 10 kg of Sn ingot, 25 kg of Cu-Si (Si20%), 1 kg of Cu-P (P14%), 0.5 kg of rare earth, and 404 kg of zinc ingot are added into the smelting furnace for smelting. After all the raw materials are melted, they are kept warm. Then, upward continuous casting is performed to prepare a casting billet with a specification of Φ8 mm, wherein electromagnetic stirring is used during the upward continuous casting process. The alloy composition of this embodiment is shown in Table 1, and the specific parameters of the upward continuous casting are shown in Table 2.

[0050] (2) Wire drawing (large wire drawing + online annealing): Use a six-unit large wire drawing machine for Φ5mm drawing, a drawing speed of 6m / s, an annealing coefficient of 16, and an annealing voltage of 120V, and then Φ3mm drawing, a drawing speed of 8m / s, an annealing coefficient of 15, and an annealing voltage of 118V.

[0051] (3) Finished product drawing (mid-drawing + online annealing): Φ1.5mm drawing is performed using a mid-drawing machine, the drawing speed is 8m / s, the annealing coefficient is 26, and the annealing voltage is 118V.

[0052] Example 2

[0053] The preparation method of the copper alloy material in this embodiment is as follows:

[0054] (1) Perform upward continuous casting + electromagnetic stirring on the alloy melt: according to the alloy composition ratio, 561kg of cathode copper, 12kg of Sn ingot, 30kg of Cu-Si (Si20%), 1kg of Cu-P (P14%), 0.4kg of rare earth, and 396kg of zinc ingot are added into a smelting furnace for smelting. After all the raw materials are melted, they are kept warm. Then, upward continuous casting is performed to prepare a casting billet with a specification of Φ8mm, wherein electromagnetic stirring is used during the upward continuous casting process. The alloy composition of this embodiment is shown in Table 1, and the specific parameters of the upward continuous casting are shown in Table 2.

[0055] (2) Wire drawing (large wire drawing + online annealing): Use a six-unit large wire drawing machine for Φ5mm drawing, a drawing speed of 7m / s, an annealing coefficient of 17, and an annealing voltage of 123V, and then Φ3mm drawing, a drawing speed of 8m / s, an annealing coefficient of 18, and an annealing voltage of 126V.

[0056] (3) Finished product drawing (mid-drawing + online annealing): Φ1.5mm drawing is performed using a mid-drawing machine, the drawing speed is 8m / s, the annealing coefficient is 26, and the annealing voltage is 118V.

[0057] Example 3

[0058] The preparation method of the copper alloy material in this embodiment is as follows:

[0059] (1) Perform upward continuous casting + electromagnetic stirring on the alloy melt: according to the alloy composition ratio, 569kg of cathode copper, 9kg of Sn ingot, 20kg of Cu-Si (Si20%), 1kg of Cu-P (P14%), 0.4kg of rare earth, and 400kg of zinc ingot are added into the smelting furnace for smelting. After all the raw materials are melted, they are kept warm. Then, upward continuous casting is performed to prepare a casting billet with a specification of Φ8mm, wherein electromagnetic stirring is used during the upward continuous casting process. The alloy composition of this embodiment is shown in Table 1, and the specific parameters of the upward continuous casting are shown in Table 2.

[0060] (2) Wire drawing (large wire drawing + online annealing): Use a six-unit large wire drawing machine for Φ5mm drawing, a drawing speed of 6m / s, an annealing coefficient of 15, and an annealing voltage of 118V, and then Φ3mm drawing, a drawing speed of 8m / s, an annealing coefficient of 15, and an annealing voltage of 118V.

[0061] (3) Finished product drawing (mid-drawing + online annealing): Φ1.5mm drawing is performed using a mid-drawing machine, the drawing speed is 7m / s, the annealing coefficient is 27, and the annealing voltage is 121V.

[0062] Comparative Example 1

[0063] The brand is BCu60ZnSnSi, Cu: 60, Sn0.8, Si0.35, Zhejiang Huayang solder, and its preparation process is: semi-continuous casting + extrusion + wire drawing + annealing + wire drawing, as follows:

[0064] (1) Semi-continuous casting smelting: All elements are added in percentage by weight. The remaining cathode copper and zinc ingots with a purity of more than 99.99% are added to the medium frequency induction furnace and heated and melted under the protection of charcoal covering agent. After the cathode copper is completely melted, a tin block with a purity of 99.9% wrapped in copper skin is added to the bottom of the furnace, followed by the addition of copper-silicon master alloy. The temperature is then raised to 1100°C, and a stone mill is used for stirring and refining. The furnace temperature is then raised to 1260°C, the pulling speed is 60 mm / min, the water inlet temperature is 25°C, the water outlet temperature is 30°C, the cooling water flow rate is 10-15 m3 / h, and the copper ingot size is Ф195 mm.

[0065] (2) Extrusion: The copper alloy ingot obtained in step (1) is placed in a gas furnace, heated to 670° C., and then subjected to reverse extrusion deformation processing; the extrusion deformation processing is carried out on a 2200t extruder, the extrusion is a reverse extrusion method, and the extrusion die size is Φ6 mm.

[0066] (3) Pickling: The extruded blank obtained in step (2) is pickled by placing the extruded blank in a tank containing 25% sulfuric acid + 5% nitric acid for pickling to remove surface oxides and oil stains.

[0067] (4) Wire drawing: Inverted wire drawing is then performed, with a wire drawing speed of 40 m / min and a wire drawing specification of Φ4.5 mm.

[0068] (5) Annealing: annealing in a bell furnace, heating for 2 h, keeping warm for 3 h, annealing temperature 510 °C.

[0069] (6) Pickling: The annealed sample is pickled under the same pickling conditions as in step (3).

[0070] (7) Wire drawing: The pickled sample is subjected to wire drawing in the same manner as in step (4), and the wire drawing specification is Φ3 mm.

[0071] (8) Annealing: The annealing conditions are the same as those in step (5).

[0072] (9) Pickling: The pickling conditions are the same as those in step (3).

[0073] (10) Vertical wire drawing: wire drawing speed 60m / min, wire drawing specification Φ2mm.

[0074] (11) Vertical wire drawing: Repeat step (10), wire drawing specification Φ1.5mm.

[0075] Comparative Example 2

[0076] The alloy composition of Comparative Example 2 is shown in Table 1, and its preparation process is the same as that of Comparative Example 1 (semi-continuous casting+extrusion+wire drawing+annealing+wire drawing).

[0077] Comparative Example 2 adopts the process route of semi-continuous casting + extrusion + wire drawing + annealing + wire drawing. The first production cycle is longer and the number of annealing times increases, which will lead to a greater degree of Si element aggregation, making the material brittle and the weld brittle.

[0078] The microstructure properties and physical properties of the finished products of the embodiments of the present invention and the comparative examples are shown in Table 3 and Table 4, respectively.

[0079] After welding the materials of the embodiments of the present invention and the comparative examples, the weld air tightness test was performed. After the parts were sealed, they were placed in water for a pressure test to see if any bubbles emerged. The problematic parts were then subjected to ultrasonic testing to determine the defect type. The number of parts tested was 100 per group. The results are shown in Table 5.

[0080] Table 1 Alloy composition of the embodiments of the present invention and the comparative examples

[0081] element Cu% Sn% Si% P% Rare earth elements% Zn% Example 1 59.3 0.9 0.3 0.005 La:0.05 margin Example 2 58.6 0.8 0.4 0.004 Ce: 0.04 margin Example 3 57.9 1.1 0.5 0.008 La: 0.04 margin Comparative Example 1 60 0.8 0.35 / / margin Comparative Example 2 58.6 0.8 0.3 0.006 Ce: 0.05 margin

[0082] Table 2 Melting parameters of the embodiments of the present invention and the comparative examples

[0083]

[0084] Table 3 Microstructure properties of finished products of the embodiments of the present invention and the comparative examples

[0085]

[0086] Table 4 Physical properties of the finished products of the embodiments of the present invention and the comparative examples

[0087]

[0088] Table 5 Test results of weld air tightness after welding of materials in the embodiments of the present invention and the comparative examples

[0089]

Claims

1. A copper alloy material, characterized in that: The copper alloy material comprises the following components in percentage by mass: Cu: 56-64%, Sn: 0.5-2.0%, Si: 0.1-1.0%, and the balance is Zn and inevitable impurities, wherein the content of inevitable impurities is ≤0.1%; the microstructure of the copper alloy material comprises α phase, β phase, Sn phase and Si phase, wherein the area ratio of α phase is 10%≤≤30%, the area ratio of β phase is 60%≤≤80%, 5000 pieces / mm 2 ≤Sn particles ≤20000 / mm 2 , 2000 pieces / mm 2 ≤ Number of Si particles ≤ 10000 / mm 2 .

2. The copper alloy material according to claim 1, characterized in that: The copper alloy material includes P, and the content of P is 0.001-0.3%.

3. The copper alloy material according to claim 2, characterized in that: The copper alloy material includes a Cu3P phase, and the area ratio of the Cu3P phase satisfies: 0.2%≤Cu3P phase area ratio≤3%.

4. The copper alloy material according to claim 1, characterized in that: The oxygen content in the copper alloy material is ≤20ppm.

5. The copper alloy material according to claim 1, characterized in that: The copper alloy material includes rare earth elements, and the content of the rare earth elements is 0.01-0.1%; the rare earth elements preferably include at least one of La, Ce or Y.

6. The copper alloy material according to claim 1, characterized in that: The volume resistivity of the copper alloy material is ≤0.07Ω·mm 2 / m, melting point ≤860℃.

7. The copper alloy material according to any one of claims 1 to 6, characterized in that: The copper alloy material is copper alloy welding wire.

8. The method for preparing the copper alloy material according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: performing upward continuous casting on the alloy melt + electromagnetic stirring → large wire drawing + first online annealing → medium wire drawing + second online annealing; Among them, the drawing speed of the large wire drawing is 6-10m / s, the annealing coefficient of the first online annealing is 10-20kU%, and the annealing voltage is 100-130V; the drawing speed of the medium wire drawing is 3-14m / s, the annealing coefficient of the second online annealing is 25-30kU%, and the annealing voltage is 90-125V.

9. The preparation method according to claim 8, characterized in that: The processing rate of the large wire drawing is ≥40%.

10. Use of the copper alloy material according to any one of claims 1 to 7 in the field of welding.

Citation Information

Patent Citations

  • Pressure-resistant and corrosion-resistant copper alloy, brazed structure, and method for producing brazed structure

    CN103154284A

  • Lead-free free-to-cut brass and preparation method thereof

    CN112226645A

  • Wrought copper-zinc alloy, semi-finished product formed of a wrought copper-zinc alloy and method for producing a semi-finished product of this type

    TW202407110A

Cited By

  • Pseudo-ginseng brass for bullets and preparation method thereof

    CN120606065A